The two sides of innovation : creation and destruction in the evolution of capitalist economies - Cantner, Uwe; Hanusch, Horst; Hutter, Michael; Lorenz, Hans-Walter; Rahmeyer, Fritz (Economic Complexity and Evolution, 2013)
This volume is devoted to innovation with a special focus on its two sides, namely creation and destruction, and on its role in the evolution of capitalist economies. The first part of the book looks at innovation and its effects on economic performance, addressing issues of motives, behavioral rules under uncertainty, actor properties, and technology characteristics. The second part concentrates on potential consequences of innovative activities, in particular structural change, the "innovation-mediated" effect of skill-oriented policies on regional performance, the destructive effects of innovation activities, and the question whether novelty is always good. The role of innovation in the evolution of capitalism itself is discussed in the third part.